Views, goals, expectations, and experiences of family and work among women and men in science: a longitudinal perspective - Scherbak, Veronica, author; Canetto, Silvia Sara, advisor; Gibbons, Alyssa, committee member; Lucas-Thompson, Rachel, committee member (Colorado State University. Libraries, 2021)
In the United States women are underrepresented in many science fields, particularly in leadership positions. It has been theorized that work-family interface issues, including those related to having a spouse and children, are a critical challenge for women in science. Having a spouse and children, however, is not an experience unique to women in science, therefore theoretically at least, work-family interface issues are issues for men in science as well. Research on the work-family interface has primarily focused on women so it is less clear how men in science deal with work-family interface. Other limitations of the research on work-family interface are that it has been mostly cross-sectional and mostly focused on the undergraduate or the professional stages, with less information being available about the graduate and early post-doctoral years. This study examined female and male scientists' views, goals, expectations, and experiences of work, marriage and parenthood at two points in their educational and work trajectory, the first being the graduate-program stage, and the next being a few years later. Interviews with 8 scientists (4 women, 4 men) who were in a committed heterosexual relationship at time 1, and married by time 2 were conducted. In addition to the interviews, the participants completed a questionnaire about their educational, career and family background. The time 1 findings in terms of work, marriage and parenting were consistent with those of previous studies. Female scientists expressed gratitude to their partner, while male scientists appeared to expect the support they received from their partner. Female scientists planned to make, and made accommodations for their partner's careers. Male scientists did not, and treated their careers as a priority. Female scientists viewed raising their children as their responsibility. Male scientists discussed investing in their careers as the means to fulfill their responsibility toward their children. The male scientists described family time mostly as a reprieve from work, not as another kind of work. By time 2, a polarizing shift in work, marriage, and parenting priorities and behavior was observed among both female and male scientists. For female scientists the shift coincided with the transition to being a mother. Female scientists talked about their science career as secondary to their partner's career. They also took on the majority or all childcare tasks. In contrast, male scientists had increased investment in their own career. Limitations of this study include that participants self-selected in the study and also that only one person from the couple was interviewed. The strengths include that this study focused on one field, that it was longitudinal, and that it included female and male scientists. This study's findings, together with those of related studies, suggest that two of the reasons that women are underrepresented in science leadership is that they are socialized to, and therefore often make career sacrifices to accommodate their family—including, in heterosexual couples, giving priority to their male partners' employment and taking responsibility for most if not all childcare. By contrast, men are socialized to, and therefore often invest in paid work as a way to fulfill both work and family responsibilities--which for male scientists in heterosexual couples often means having a career minimally or completely not encumbered by family responsibilities.